2011
DOI: 10.1371/journal.pone.0016319
|View full text |Cite
|
Sign up to set email alerts
|

HNF4alpha Dysfunction as a Molecular Rational for Cyclosporine Induced Hypertension

Abstract: Induction of tolerance against grafted organs is achieved by the immunosuppressive agent cyclosporine, a prominent member of the calcineurin inhibitors. Unfortunately, its lifetime use is associated with hypertension and nephrotoxicity. Several mechanism for cyclosporine induced hypertension have been proposed, i.e. activation of the sympathetic nervous system, endothelin-mediated systemic vasoconstriction, impaired vasodilatation secondary to reduction in prostaglandin and nitric oxide, altered cytosolic calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In smooth muscle cells, cyclosporine caused a twofold increase in the number of angiotensin II type 1 receptors, suggesting that the effects of angiotensin II could be augmented, even when its plasma levels are unchanged (39). More recently, one study suggested that inhibition of NFATc by CNIs represses the hepatic nuclear factor 4 alpha and that this would activate angiotensin II type 1 receptors to cause vasoconstriction (40). …”
Section: Vascular Effects Of Calcineurin Inhibitorsmentioning
confidence: 99%
“…In smooth muscle cells, cyclosporine caused a twofold increase in the number of angiotensin II type 1 receptors, suggesting that the effects of angiotensin II could be augmented, even when its plasma levels are unchanged (39). More recently, one study suggested that inhibition of NFATc by CNIs represses the hepatic nuclear factor 4 alpha and that this would activate angiotensin II type 1 receptors to cause vasoconstriction (40). …”
Section: Vascular Effects Of Calcineurin Inhibitorsmentioning
confidence: 99%
“…However, long term treatment with CsA is frequently complicated by systemic and renal vasoconstriction, leading to arterial hypertension (Curtis, 2002). Although numerous factors have been implicated in the development of CsA-induced hypertension (Hoorn et al, 2012;Niehof and Borlak, 2011), the molecular mechanisms remain obscure. Our previous study with organ culture system showed that CsA upregulated both mRNA expression and contractile function of endothelin B receptor (ET B ) in vasculature (Zheng et al, 2013), but the underlying mechanisms were not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, the usage of CsA is accompanied by mild to severe side effects, and the clinically most important are nephrotoxicity and hypertension . There is definitive proof for cyclosporine to increase blood pressure in human beings and animals , and the underlying mechanisms by which CsA causes arterial hypertension after kidney transplantation are related to the activation of the sympathetic nervous system , the increased vasoconstriction and the impaired vasodilatation . Although the molecular mechanisms for CsA‐induced hypertension are still under active investigation, it is hampered by the lack of suitable in vitro models to study the roles of specific signalling pathway in CsA‐induced vascular pathogenesis.…”
mentioning
confidence: 99%